Daur al-Biah al-Lugawiyyah fī Tarqiyah al-Kafāah al-Żātiyyah li al-Kalām ladai Ṭalabah al-Madrasah al-Ṡānawiyyah - Miftahudin, Miftahudin; Harisca, Rodhi; Khoirurrijal, Khoirurrijal (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research The purpose of this research. First, the state of the linguistic environment in increasing speaking self-efficacy among MTs Mambaul Ulum Metro students is to be determined. Second, to find out the application of speaking efficacy training to MTs Mambaul Ulum Metro students. Third, to reveal self-efficacy in speaking to MTs Mambaul Ulum Metro students. This research methodology is a descriptive qualitative study that describes and finds appropriate and precise facts. Moreover, how to collect data using interviews, observation, and written document methods. This study examines the language environment's role in enhancing students' subjective speaking skills at MTs Manbaul Ulum Metro. By employing qualitative research methods, including observations and interviews, the study explores how various aspects of the language environment contribute to students' perceptions of their speaking abilities. The findings reveal that a supportive language environment, characterized by frequent practice opportunities, positive reinforcement, and exposure to diverse linguistic inputs, significantly boosts students' confidence and proficiency in speaking. The study underscores the importance of creating a conducive language learning environment to facilitate effective language acquisition. The language environment system at MT Mambaul Ulum Metro School is very important to increase student's confidence in speaking Arabic through active interaction and correct use of grammar. Social support, a supportive learning environment, the use of technology, and effective learning strategies play a role in building students' self-confidence. Consistent speaking practice and real-world activities such as a language classroom environment. These factors help students develop courage, perseverance, and the ability to face the challenges of learning Arabic.